Dream big : Michael Jordan and the pursuit of excellence - Jordan, Deloris; Root, Barry (New York : Simon & Schuster Books for Young Readers, 2014)
From the age of nine years Michael dreams of playing basketball for the United States in the Olympics, and with hard work and his mother's encouragement, he realizes his dream.
"Previously published as Dream big : Michael Jordan and the pursuit of Olympic gold."
"A Paula Wiseman book."
Keywords: Jordan, Michael, -- 1963- -- Childhood and youth -- Juvenile fiction; Jordan, Michael, -- 1963- -- Childhood and youth -- Fiction; Jordan, Michael, -- 1963- -- Fiction; Basketball -- Fiction; Basketball stories; Basketball -- Fiction